1996
DOI: 10.1016/s0090-4295(96)00206-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between uroflowmetry, prostate volume, postvoid residue, and lower urinary tract symptoms as measured by the international prostate symptom score

Abstract: Objectives. To evaluate the relation between lower urinary tract symptoms (LUTS) as measured by the International Prostate Symptom Score (IPSS) and noninvasive objective parameters of lower urinary tract dysfunction. Methods. Eight hundred three consecutive patients with LUTS and/or benign prostatic hyperplasia were evaluated with IPSS, uroflowmetry, prostate volume estimation, and postvoiding residue measurement. The relations between these parameters were quantified by means of Spearman correlation coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 10 publications
9
57
0
4
Order By: Relevance
“…10 Another study by Tsukamoto et al showed that a change in IPSS was associated with a change in prostate volume, 11 whereas study by Agrawal et al, Sanjeev singla et al, Udeh et al, and Ezz et al showed no relationship between prostate size and IPSS score. 6,8,12,13 There was no correlation between the age and IPSS in our study, which is similar with Agrawal et al, but Bosch JL et 14 states that very weak correlation between the IPSS and age (r = 0.09, P = 0.04). There is lot of variations in the findings by different authors, but most of studies found no strong correlation between the IPSS and prostate volume.…”
Section: Discussionsupporting
confidence: 89%
“…10 Another study by Tsukamoto et al showed that a change in IPSS was associated with a change in prostate volume, 11 whereas study by Agrawal et al, Sanjeev singla et al, Udeh et al, and Ezz et al showed no relationship between prostate size and IPSS score. 6,8,12,13 There was no correlation between the age and IPSS in our study, which is similar with Agrawal et al, but Bosch JL et 14 states that very weak correlation between the IPSS and age (r = 0.09, P = 0.04). There is lot of variations in the findings by different authors, but most of studies found no strong correlation between the IPSS and prostate volume.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, no correlation was found in between prostatic volume and IPSS. This data was further supported by other studies which were done by Ezz et al, on 803 patients [12].…”
Section: Discussionsupporting
confidence: 87%
“…At present, the most utilized method to confirm infravesical obstruction is the pressure / flow study (12)(13)(14)(15)(16). Urodynamics distinguish low flow secondary to hypoactivity of the detrusor from the low flow caused by obstruction.…”
Section: Discussionmentioning
confidence: 99%